PERBANDINGAN METODE SAW DAN TOPSIS DALAM SISTEM PENDUKUNG KEPUTUSAN PENERIMA BANTUAN LANGSUNG TUNAI DI DESA LAMONGAN - Moh. Alfian Husni Mubarok; Dewi Khoirunisak; Rahmat Hidayatullah; Nur Azise (LPPM Universitas Dhyana Pura, 2025)
The selection process for Direct Cash Assistance recipients in Lamongan Village is still conducted manually, leading to subjectivity and mistargeting. This study compares two Decision Support System (DSS) methos-Simple Additive Weighting (SAW) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) - to improve objectivity and efficiency in BLT selection. Five criteria were applied: income, housing, condition, health, number of dependents, and age, each assigned a weight based on importance. Data were collected 15 residents recommended by local leader. SAW determines preference scores through normalization and weighted summation, while TOPSIS calculates the distance of each alternative to positive and negative ideal solutions. Both methods identified the same top recipient, Yeni Avantari, with preference scores of 0.775 (SAW) and 0.819 (TOPSIS). Although their scores differ, both methods produced consistent and fair result. The study concludes that SAW and TOPSIS are equally effective in delivering accurate, objective, and well targeted decisions in BLT distribution.